Da'wah and Social Change: Da'wah and Political Reform of the Prophet Muhammad SAW in the Implementation of the Study of the Prophet's Political Communication in Medina - Yushardiansyah, Rezsa (STAI AL-FALAH CICALENGKA, 2023)
The influence of the Prophet Muhammad as the bearer of the Islamic message is known plural. It is also about his prophetic and apostolic. The thing that is rarely discussed is Muhammad's position as a political communicator. In this case Muhammad is certainly an actor in the process of political communication in Medina. History calls the long journey of forming the Medina State under the reign of Muhammad starting from zero to become an area that was calculated at that time. It is not excessive for Muhammad to be called as a political actor in the establishment of Medina as well as political communicator in the government of Medina. In political communication, it is mentioned that political actors can form a public opinion, which then becomes consensus and mutually agreed. Thus, Muhammad has fulfilled that element in his leadership over Medina. In the process of political communication, there are important elements such as political communicators, messages delivered, and targets to the political communication effect that made Muhammad in Medina. The interesting thing for studied is Muhammad's political communication strategy. Where is as a political communicator, Muhammad was able to unite the heterogeneity and pluralism of the community who then agreed and want to be under his leadership in Medina. Keywords: political communication, Medina, Muhammad, country. Abstrak Pengaruh Nabi Muhammad sebagai pembawa risalah Islam dikenal jamak. Ini juga tentang kenabian dan apostoliknya. Hal yang jarang dibicarakan adalah posisi Muhammad sebagai komunikator politik. Dalam hal ini Muhammad tentunya merupakan aktor dalam proses komunikasi politik di Madinah. Sejarah menyebut perjalanan panjang terbentuknya Negara Madinah di bawah pemerintahan Muhammad dimulai dari nol hingga menjadi wilayah yang diperhitungkan saat itu. Tidak berlebihan jika Muhammad disebut sebagai aktor politik pendirian Madinah sekaligus komunikator politik dalam pemerintahan Madinah. Dalam komunikasi politik disebutkan bahwa aktor politik dapat membentuk opini publik yang kemudian menjadi konsensus dan disepakati bersama. Dengan demikian, Muhammad telah memenuhi elemen tersebut dalam kepemimpinannya atas Madinah. Dalam proses komunikasi politik terdapat unsur-unsur penting seperti komunikator politik, pesan-pesan yang disampaikan, dan sasaran terhadap efek komunikasi politik yang dilakukan Muhammad di Madinah. Hal yang menarik untuk dikaji adalah strategi komunikasi politik Muhammad. Dimana sebagai komunikator politik, Muhammad mampu menyatukan heterogenitas dan pluralisme masyarakat yang kemudian setuju dan ingin berada di bawah kepemimpinannya di Madinah. Kata kunci: komunikasi politik, Madinah, Muhammad, negara.